Practical aspects in first aid cooling of burns - Venter, Tertius Hendrik Johannes (Division of Plastic and Reconstructive Surgery, 2024)
The beneficial effects of first aid cooling of fresh burn wounds have been recognised for many years, particularly with regard to the relief of pain, but there still exists controversy as to the effects of cooling in limiting the damage and the influence on subsequent healing in the burn wound. This might be influenced by the temperature of the coolant, the time delay from the injury to commencement of cooling, how effectively the coolant is applied and the time period of cooling. Four identical burn wounds were created on the back of an anaesthetized pig. One wound was not cooled and the other three wounds cooled,· two with a time delay of half an hour and one immediately, each of the three for different periods of time. Eleven pigs were used and each pig served as an independent experimental model. The animals were farther divided in two groups,· Group I using ice water to cool the wounds and Group II using tap water,· Group Ila using slightly warmer water than group Ilb. It was found that the temperature of the coolant was crucial if applied effectively. An effective method of cooling of fresh burn wounds is demonstrated. When ice water of 1-8 degrees celsius (Group I) was used it caused more damage than in the wounds that were not cooled. When tap water was used at 12-18 degrees celsius (Group II) to cool the wounds it could be demonstrated clinically and histologically that the cooled wounds had less damage than the uncooled wounds and healed faster. In group II it was shown that the beneficial effects of cooling was still present in the wounds where commencement of cooling was delayed for half an hour.